Impacts of the Substitutability of Consumption on Infection Dynamics - Fukuda, Shin (International Journal of Economics and Financial Issues, 2023)
In this study, we construct a dynamic stochastic general equilibrium (DSGE) model to examine the impacts of infectious diseases on consumption dynamics. Assuming a model that considers the substitutability of consumption, we show that the slump in demand for consumption goods will be low in high-substitutability economy. Further, we show that immediate lockdown implementation upon the emergence of an epidemic can lead to a significant reduction in consumption, as well as alleviate the persistent stagnation of consumption, Although the analysis model in this study is simple, it reproduces the situations in United States and Japan, and it could be said that the impact of contingent policies, such as lockdown, has already been confirmed in Taiwan and New Zealand.